A Study of Drug Abuse Prevention and Law Enforcement in Indonesia From The Persperctive of Social Control and Neurocriminology - Pratiwi, Utari Dwi; Hanita, Margaretha; Iskandar, Kurniawaty (Technium Social Sciences Journal, 2023)
Indonesia as a good market and good price, meaning that Indonesia is considered a good market and also has good business prospects for the circulation of these prohibited goods. Drug cases during the COVID-19 pandemic have increased significantly. Drug dealers take advantage of the momentum of the COVID-19 pandemic by distributing drugs in Indonesia. Innovation is needed in the current narcotics problem. This research aims to describe the situation and conditions of drug abuse in Indonesia during the COVID Pandemic, the criminalization of drug abuse in the perspective of neurocriminology and the prevention of drug abuse in the inherent supervision of the community. The writing method uses a qualitative method with a literature study model. The results show that neurocriminology can be used in sentencing drug abusers for rehabilitation while social control theory can be used in prevention efforts involving the community.